Phase IIb Trial of an α7 Nicotinic Receptor Partial Agonist With and Without Nicotine Patch for Withdrawal-Associated Cognitive Deficits and Tobacco Abstinence. Issue 4 (August 2018) - Schuster, Randi Melissa; Pachas, Gladys N.; Stoeckel, Luke; Cather, Corinne; Nadal, Mireya; Mischoulon, David; Schoenfeld, David A.; Zhang, Haiyue; Ulysse, Christine; Dodds, Elisabeth B.; Sobolewski, Sara; Hudziak, Vicenta; et al.
Abstract: Purpose/Background: The objective of this study was to determine whether a novel α7 nicotinic acetylcholine receptor partial agonist improves cognition during nicotine withdrawal and improves abstinence rates. To do so, the effect of the α7 nicotinic acetylcholine receptor partial agonist, encenicline, on cognition and abstinence was evaluated when given as monotherapy and when combined with transdermal nicotine patch (nicotine replacement therapy [NRT]). Methods: Adult daily smokers, n = 160, who were motivated to quit smoking completed cognitive testing at satiated baseline and after overnight abstinence and then were randomized to receive a 12-week trial of encenicline 1 mg twice daily or identical placebo the day of the overnight abstinent cognitive testing. In the first 6 weeks of the 12-week encenicline administration, participants were also randomized to 6 weeks of NRT patch or placebo patch. Primary outcomes were cognition during abstinence and 7-day point-prevalence abstinence at week 12. Results: No beneficial effects of encenicline were observed on cognition or abstinence when compared with placebo or when combined with NRT compared with placebo capsule + NRT. Of the 4 conditions, abstinence rates were lowest among those assigned to encenicline alone. Conclusions: Beneficial effects of NRT were observed on cognitive and abstinence outcomes when combined with encenicline compared with encenicline plus placebo patch. Addition of NRT to encenicline improved odds of abstinence approximately 3-fold compared with encenicline plus placebo patch. We conclude that encenicline, 1 mg/d, did not improve abstinence-associated cognitive impairment or abstinence rates as monotherapy or adjunctive therapy to NRT patch. Abstract : Supplemental digital content is available in the text.